Financial system stability, the timing of climate change action and the Federal Reserve - Carolin D. Schellhorn (Journal of Central Banking Theory and Practice, 2020)
Timely and effective climate action is a precondition for the stability of the global financial system and for long-term, inclusive prosperity. Because the Federal Reserve and other central banks share responsibility with legislative and regulatory authorities and other experts for maintaining financial system stability, the Fed also shares responsibility for effective climate action. For climate action to be effective in reducing greenhouse gas emissions and limiting global warming, it must be widespread, it must be substantive, and it must come sooner rather than later. The new low-interest rate monetary policy environment favors sustainable long-term, but also high-risk, investments. Market participants need timely guidance and support from regulatory and supervisory authorities, including the Federal Reserve, in order to expedite global fund allocations to low-carbon assets.
Keywords: E44; E58; 330; Climate Change; Central Bank Independence; Federal Reserve; Financial System Stability; Low-Carbon Transition